Drug Testing of Juvenile Detainees to Identify High-Risk Youth in Florida, 1986-1987 - Dembo, Richard ([Verlag nicht ermittelbar], 1992)
This data collection examines the interrelationships among drug/alcohol use, childhood sexual or physical abuse, and encounters with the juvenile justice system. To identify high-risk individuals, youths in a Tampa juvenile detention center were given urine tests and were asked a series of questions about past sexual and/or physical abuse. Official record searches were also conducted 6, 12, and 18 months afterward to measure later encounters with the juvenile or criminal justice systems. The investigators used the youths' urine test results as the primary measure of drug use. On the basis of their review of Florida's statutes, the investigators developed outcome measures for the following offense categories: violent felonies (murder/manslaughter, robbery, sex offenses, aggravated assault), property felonies (arson, burglary, auto theft, larceny/theft, stolen property offenses, damaging property offenses), drug felonies (drug offenses), violent misdemeanors (sex offenses, nonaggravated assault), property misdemeanors (larceny/theft, stolen property offenses, damaging property offenses), drug misdemeanors (drug offenses), and public disorder misdemeanors (public disorder offenses, trespassing offenses). Other variables measured physical and sexual abuse, emotional and psychological functioning, and prior drug use. Demographic variables on sex, race, age, and education are also contained in the data. The individual is the unit of analysis.